Advancing Interprofessional Primary Health Care Teams in Québec: A Policy Analysis - Paul Wankah; Aisha Zerbo (Health Reform Observer – Observatoire des Réformes de Santé, 2026)
Québec’s primary health care system has undergone significant reforms with family medicine groups (GMFs) introduced in 2002 as interprofessional team-based care models. Initially comprising family physicians and nurses, a policy shift in 2016 allocated allied health professionals (AHPs) including social workers, pharmacists, occupational therapists, among others, to GMFs. Kingdon’s multiple streams analysis shows the problem stream (growing patient complexity and persistent access gaps), the policy stream (evidence supporting interprofessional care) and the politics stream (sustained political commitment to primary care reforms) converged to create a policy window to enable the allocation of AHPs to GMFs in Québec. However, implementation has been uneven, marked by role ambiguity, delayed supports, and governance tensions. This analysis contributes to understanding health workforce policy change in primary health care, highlighting the necessity for stronger evaluation and implementation supports to ensure the sustainability of interprofessional primary care. Le système de soins de première ligne du Québec a connu d’importantes réformes, notamment avec la création des groupes de médecine de famille (GMF) en 2002 comme modèle de soins interprofessionnels. Initialement composés de médecins de famille et d’infirmières, les GMF ont connu un tournant en 2016 avec l’intégration de professionnels de la santé et des services sociaux, incluant notamment des travailleurs sociaux, pharmaciens et ergothérapeutes. L’analyse des multiples courants de Kingdon montre que la convergence du courant des problèmes (complexification des besoins et lacunes d’accès), du courant des politiques (preuves en faveur des soins interprofessionnels) et du courant politique (engagement soutenu envers les réformes des soins primaires) a ouvert une fenêtre d’opportunité pour cette transformation. Toutefois, la mise en œuvre demeure inégale, marquée par une ambiguïté des rôles, des soutiens tardifs et des tensions de gouvernance. Cette analyse met en lumière la nécessité de renforcer l’évaluation et les mécanismes de mise en œuvre pour assurer la durabilité des soins primaires interprofessionnels.